2021
DOI: 10.12688/wellcomeopenres.16344.3
|View full text |Cite
|
Sign up to set email alerts
|

Implication of backward contact tracing in the presence of overdispersed transmission in COVID-19 outbreaks

Abstract: Introduction: Contact tracing has the potential to control outbreaks without the need for stringent physical distancing policies, e.g. civil lockdowns. Unlike forward contact tracing, backward contact tracing identifies the source of newly detected cases. This approach is particularly valuable when there is high individual-level variation in the number of secondary transmissions (overdispersion). Methods: By using a simple branching process model, we explored the potential of combining backward contact tracing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 18 publications
3
48
1
1
Order By: Relevance
“…However, even with just forward tracing, epidemic control is still theoretically achievable. Several recent studies have produced similar findings 26 , 29 , 30 .…”
Section: Resultssupporting
confidence: 62%
“…However, even with just forward tracing, epidemic control is still theoretically achievable. Several recent studies have produced similar findings 26 , 29 , 30 .…”
Section: Resultssupporting
confidence: 62%
“…Once adapted to the UK policy, we used our model to assess the effectiveness of a ‘backwards tracing’ strategy, which aims to identify a case's infector and allows for the identification of more branches of transmission when compared to forwards tracing. We, and other groups [ 35 , 36 ], found that in theory it could improve contact tracing, but also that implementation challenges could reduce this effect. Ultimately, the NHS Test and Trace programme in England continued to use forwards tracing for standard cases not associated with a particular list of high-risk settings.…”
Section: In Contextmentioning
confidence: 89%
“…Backwards contact tracing is when the direction of tracing is opposite to the direction of transmission, which results in the traced individual being the infector of the case who initiated the tracing attempt. For some diseases, backwards tracing can be an important strategy as a backwards step can then be followed by a forwards tracing step again to discover ‘sibling’ infections who share the same infector [ 35 ]. A visualization of backwards and forwards tracing is plotted in figure 1 , where a successful backwards tracing event leads to the quarantine of a sibling chain of transmission.…”
Section: Contact Tracing Isolation Strategies and Considerations Post-lockdownmentioning
confidence: 99%
“…It may not be easily extensible to settings such as schools or workplaces. Alternative strategies also exist, including tracing of contacts-of-contacts [ 38 ] and so-called backwards tracing [ 39 ]. The latter approach is part of a fundamentally different way of using contact tracing in disease control that has been used in COVID-19 response in some countries (e.g., Japan [ 40 ]), which focuses on identifying settings that have the potential to facilitate superspreading events or otherwise amplify transmission.…”
Section: Discussionmentioning
confidence: 99%